2010
DOI: 10.1038/gene.2010.16
|View full text |Cite
|
Sign up to set email alerts
|

CTLA4 −1661A/G and 3′UTR long repeat polymorphisms are associated with ulcerative colitis and influence CTLA4 mRNA and protein expression

Abstract: Reduced cytotoxic T-lymphocyte antigen 4 (CTLA4) expression has been proposed as a risk for autoimmunity. CTLA4 polymorphisms have been associated with several autoimmune diseases, including ulcerative colitis (UC). In this study, we performed genotyping for CTLA4 À1661A/G, À1722T/C and 3 0 untranslated region (AT)n repeat polymorphisms in 300 Chinese UC patients and in 700 healthy controls, and evaluated the effects of polymorphisms on full-length (flCTLA4) and soluble CTLA4 (sCTLA4) expression in UC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Semi-quantitative analysis of staining intensity for the HSF2 protein was performed using the HPIAS-2000 image analysis software (Tongji Qianping Imaging Inc., Wuhan, China) according to Chen [15] and Wang et al [16]. In brief, four highly magnified visual fields (10×40 magnification) (with no overlap) from each tissue section were randomly selected, and theirs digitalized images were submitted to the image analysis software.…”
Section: Methodsmentioning
confidence: 99%
“…Semi-quantitative analysis of staining intensity for the HSF2 protein was performed using the HPIAS-2000 image analysis software (Tongji Qianping Imaging Inc., Wuhan, China) according to Chen [15] and Wang et al [16]. In brief, four highly magnified visual fields (10×40 magnification) (with no overlap) from each tissue section were randomly selected, and theirs digitalized images were submitted to the image analysis software.…”
Section: Methodsmentioning
confidence: 99%
“…So far, little is known about the IL-23/Th17 pathway in Chinese IBD patients, and many studies illustrate that genetic mutations that predispose to IBD appear to vary between different geographical and racial groups [6, 7]. Thus, our previous study examined the distribution of 26 SNPs of UC and 18 SNPs of CD in the IL-23/Th17 pathway genes in Chinese IBD patients and found that the polymorphisms of IL-12B, IL23R, JAK2, and TNFSF15 are strongly associated with Chinese IBD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Abatacept, which inhibits T-cell costimulation (CTLA4-Ig), was theorized to be useful in IBD, as CTLA4 polymorphisms may play a role in pathogenesis of the disease [87,88]. However, a Phase 3 study (NCT00406553) among patients with Crohn's Disease was terminated due to lack of efficacy.…”
Section: Treatmentmentioning
confidence: 96%